Entre sens et mémoire. Philosophie et littérature de la Shoah - Bensussan, Gérard (Filosofia Morale/Moral Philosophy, 2024)
The universal language of philosophy, namely the logos, runs out in an effort to procure an intelligibility to the Shoah, in an attempt to give it reasons and to inscribe it in a causal chain. The sense presides over the passage from empirical diversity to its fixing into a concept. Nonetheless, it is necessary to reaffirm that the Shoah doesn’t make any sense, although this does not exempt us from having to think it. There is no philosophy of the Shoah, even when set within a meditation on evil inasmuch evil thinks. There is however a literature of the Shoah which allows to approach a sense preceding the “sense” and to avoid the perverse demand that always asks for unquestionable evidences of an existence.